Uso de bentonita como aditivo impermeabilizante em argamassa polimérica cimentícia - Paula, Baptista Leme (2024)
Waterproofing is one of the most crucial stages in civil construction. Recent studies have reported significant improvements in the waterproofing behavior of mortars containing bentonite. However, the addition of high percentages of this additive can result in a reduction in the consistency and fluidity of mortars, affecting the hydration process of Portland cement and the final properties of the products. In this context, this dissertation aimed to evaluate the use of activated sodium or calcic bentonite as a low-cost waterproofing additive in the preparation of optimized polymeric mortars. For this purpose, the preparation of a commercial mortar and others formulated (based on ratios of 3.5:1 and 3:1 – ratio of solid:liquid components) containing varied amounts (0-6 wt.%) of activated sodium and calcic bentonite was carried out. The chosen bentonites were characterized, and the performance of the mortars was evaluated through tests of fluidity, water absorption, mechanical resistance, watertightness tests, and microstructural analysis. The results indicated differences in the chemical composition of the bentonites, with activated sodium having smaller particle size, higher reactivity, and, consequently, three times greater swelling (25 ml/2g) than calcic bentonite (8 ml/2g). In general, all analyzed mortars showed reduced flow with the addition of bentonites. Furthermore, a significant reduction (6.17%) in water absorption was observed in samples containing 6wt.% of activated sodium bentonite compared to the reference mortar. Watertightness tests confirmed the applicability of mortars prepared with 2wt.% of calcic or sodium bentonite. The incorporation of up to 2wt.% of activated sodium bentonite into the commercial formulation resulted in an 18.6% reduction in water penetration after 48 hours under positive pressure of 0.25 MPa.